Religion, beliefs, and international human rights - Lerner, Nātān 1925- (Maryknoll, N.Y Orbis Books, 2000)
"In this volume, an Israeli jurist provides an authoritative distillation and analysis of modern international norms on religious rights and liberties - with particular attention to modern controversies over religious and racial discrimination, genocide and group libel, proselytism and conversion, and religious group rights and their limits."--BOOK JACKET
Religion and Human Rights Series Preface ix -- Religious Human Rights Literature 2 -- Legal Meaning of Religion and Belief 3 -- 1. Religious Human Rights under the United Nations 9 -- Universal Declaration of Human Rights 9 -- First Specific Steps: The Krishnaswami Study (1959) 11 -- 1966 Covenants on Human Rights 15 -- United Nations Declaration on Intolerance and Discrimination Based on Religion or Belief 20 -- United Nations Declaration on Minorities 33 -- Religious Rights in Other Relevant Instruments 35 -- 2. Regional Protection of Religious Human Rights 40 -- Europe 40 -- Americas 45 -- Africa 46 -- Islam 47 -- Special and Bilateral Arrangements 48 -- 3. Protecting Religious Groups from Persecution and Incitement 51 -- Relevance of the Convention on Racial Discrimination 52 -- Group Libel 61 -- International Criminal Law 68 -- 4. Proselytism and Change of Religion 80 -- Proselytism vs. Religious Identity and Privacy 82 -- Change of Religion and Proselytism 84 -- Proselytism and Conversion in the United Nations Era 86 -- Regional Instruments 107 -- Case Law 110 -- Appendix Selected International Human Rights Instruments on Religious Human Rights 129 -- 1. Universal Declaration of Human Rights (1948) 129 -- 2. Convention on the Prevention and Punishment of the Crime of Genocide (1948) 129 -- 3. European Convention for the Protection of Human Rights and Fundamental Freedoms (1950) 129 -- 4. International Convention on the Elimination of All Forms of Racial Discrimination (1965) 130 -- 5. International Covenant on Civil and Political Rights (1966) 130 -- 6. Draft Convention on the Elimination of All Forms of Religious Intolerance (1965-1967) 131 -- 7. American Convention on Human Rights (1969) 135 -- 8. African Charter on Human and Peoples' Rights (1969) 135 -- 9. United Nations Declaration on the Elimination of All Forms of Intolerance and Discrimination Based on Religion or Belief (1981) 136 -- 10. Vienna Concluding Document (1989) 139 -- 11. Document of the Copenhagen Meeting of the Conference on the Human Dimension of the CSCE (1990) 140 -- 12. Cairo Declaration on Human Rights in Islam (1990) 140 -- 13. Declaration on the Rights of Persons Belonging to National or Ethnic, Religious, and Linguistic Minorities (1992) 140 -- 14. Fundamental Agreement between the Holy See and the State of Israel (1993) 141 -- 15. Council of Europe: Framework Convention for the Protection of National Minorities (1995) 145 -- 16. Oslo Declaration on Freedom of Religion and Belief (1998) 145.
Includes bibliographical references (p. 149-173) and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Human Rights -- Religious aspects; Religion and international relations; Menschenrechte; Religionsfreiheit; Völkerrecht; UNO/Vereinte Nationen/United Nations Organization; Internationale Abkommen; Human Rights; Religious Freedom; International Law; UN/United Nations; international agreements